CHANGES, OPPORTUNITIES, AND CHALLENGES - William M. Healy (Wildlife Society Bulletin)
Abstract: Changes in ecosystem function and human demography will present unique challenges and opportunities to natural resource managers in the near future. The function of North American forest ecosystems has been altered by introduced pathogens, loss of key species, and changed fire regimes. Management is required to sustain ecosystem function and the abundance of wildlife we enjoy. Effective management will require an interdisciplinary approach and unprecedented cooperation among management agencies. A wave of retirements will significantly reduce senior staffing of all natural resource agencies by 2010. By 2050 the United States population will be older, more urbanized, and more ethnically and racially diverse. Effective communication of resource needs and policies will require understanding public attitudes. The North American model of conservation is characterized by the wise consumptive use of wildlife. Conservation efforts would be severely weakened without the continued support of hunters, anglers, and trappers, and public support for these activities. Current hunting traditions fail to meet the social and ethical standards of the non‐hunting majority. Natural resource professionals must lead in creating a new hunting ethic that is both socially acceptable and capable of meeting ecosystem management goals.